Are CT and US imaging-guided percutaneous FNAs and/or spleen and focal splenic lesion tissue core biopsies safe and effective?. Issue 1 (January 2019) - Alonazi, Batil; Alfuhaid, Turki; Mahmoud, Mustafa Z.
ABSTRACT: The aim of this study was to evaluate the safety and effectiveness of computed tomography (CT) and ultrasound (US) imaging-guided percutaneous fine needle aspirations (FNAs) and/or spleen and focal splenic lesion tissue core biopsies in patients with splenomegaly and/or focal splenic focal lesions. The vascular interventional radiology records, clinical charts, laboratory and histopathology results of patients who underwent splenic FNAs and tissue core biopsies between January of 2016 and June of 2019 were retrospectively analyzed. These procedures success rate in making specific diagnoses and the frequency of related complications were documented. After conducting imaging-guided FNAs and tissue core biopsies, the diagnosis reached in 18 (90%) of the 20 (100%) patients. Of the 18 (90%) patients, tumoral and non-tumoral diagnoses were made in 10 (55%) and 8 (45%) patients, respectively. All procedures were achieved without major complications. In conclusion, CT and US imaging-guided percutaneous FNAs and tissue core biopsies are safe and effective for diagnosing the causes of splenomegaly and the nature of focal splenic lesions.